EFEKTIVITAS PERMAINAN IMPULSCARD DALAM MENURUNKAN IMPULSIVE BUYING BEHAVIOR IN MARKETPLACE SISWA SMA KOTA PADANG - Ikelara Aritonang; Mey Lani Rudita Lia; Salsabila Fajriati Huda; Mario Pratama (Jurnal Riset Psikologi, 2025)
This research aims to determine the effectiveness of the Impulscard game in reducing impulsive buying behavior in the marketplace among high school students in Padang City. This research uses quasi-experimental with two-group pretest-posttest design. The population is 33 high schools in Padang City that have been connected to the internet. The research sample was taken using a purposive sampling technique and obtained 6 people. The research results were analyzed using SPSS 20 software. In the experimental group, the sig. (2-tailed) value was 0.035 (<0.05) while in the control group, the sig. (2-tailed) value was 0.423 (>0.05). These results indicate that the Impulscard game is effective in reducing impulsive buying behavior in the marketplace among high school students in Padang City.